Effects Cytokinin in Seed Germination Indexes Psyllium Plantago Psyllium - Mohammad Amin Noorani (Journal of Global Pharma Technology, 2017)
Seed priming technique by which seeds under controlled conditions before being placed in their original context and this treatment before planting the exposure seeds ecological condition of the environment, physiological andbiochemical preparations not find germination This improves germination, initial establishment of the plant,earliness quality and as defense mechanisms of plants conditions. Seed dormancy treatments include the use concentrations (100, 50, 0) and kinetin concentrations (100, 50, 0) ppm. Percentage and speed of germination, germination efficiency, mean germination time, germination index, vigor index, the value germination, seedling length were measured. The results showed that in the psyllium for 100 with Kinetin Minimum germination in the passion is the same treatments. The lowest percentage in the psyllium kinetin 50.Keywords: seed dormancy, gibberellic acid, kinetin